Novel human single-domain antibodies exert potent anti-tumor activity by targeting EGF-like repeat epitope of EpCAM - Zhou, Xiaofeng; Liu, Zhifang; Zhang, Weixiong; Dai, Lin; Chen, Tao; Lin, Zexiong; Pan, Hong; Qi, Qi; Wei, Henry (Frontiers in Pharmacology, 2025)
IntroductionEpCAM (Epithelial cell adhesion molecule) is a key cancer stem cell marker involved in cancer progression, making it an important target for both diagnosis and therapy. Despite efforts using anti-EpCAM monoclonal antibodies (mAbs), their anti-tumor effects have been limited. Single-domain antibodies (sdAbs), in contrast, offer advantages such as efficient tumor penetration and reduced immunogenicity. This study aims to screen and explore novel sdAbs targeting EpCAM for cancer therapy.MethodsA critical EGF-like repeat epitope on the EpCAM extracellular domain was selected for screening a human sdAb library via phage display. The selected sdAbs were purified and their anti-cancer activity was validated through specific binding with the EpCAM peptide. The effects of these sdAbs on cell proliferation, migration, invasion, and apoptosis were tested in vitro, and their anti-tumor activity was assessed in a xenograft model.ResultsFive fully human anti-EpCAM sdAbs were isolated, all of which specifically bound to the EpCAM peptide and showed selective binding to various cancer cell lines, but not to 293T and 3T3 cells. Functional assays demonstrated that these sdAbs significantly inhibited cancer cell proliferation, migration, and invasion, and induced apoptosis. Notably, two sdAbs (aEP3D4 and aEP4G2) exhibited potent anti-tumor effects in vivo, significantly reducing tumor volume and weight in a mouse xenograft model.DiscussionThis study provides compelling evidence that targeting EpCAM with sdAbs is a promising approach for cancer treatment. The identified anti-EpCAM sdAbs exhibit substantial anti-tumor activity both in vitro and in vivo, suggesting they are strong candidates for future therapeutic applications in cancer therapy.